Exploring the Influence of Social Media Influencers on Impulse Buying Behavior of FMCG Products: A Qualitative Study - Hendry Kurniawan; Indra Iryanto Nur Hidayat (PT. Hidayat Muda Intelektual, 2025)
The increasing use of social media influencers in fast-moving consumer goods (FMCG) marketing has reshaped consumer purchasing behavior, particularly impulse buying. Unlike planned purchases, impulse buying is driven by spontaneous emotional responses and situational stimuli. This study aims to explore how social media influencers influence impulse buying behavior of FMCG products from a qualitative perspective. Using a qualitative research design, this study adopts a descriptive approach to understand consumers’ subjective experiences when exposed to influencer content. Data were collected through in-depth interviews with consumers who have purchased FMCG products impulsively after exposure to influencer recommendations on social media. The findings reveal that influencer credibility, emotional appeal, and persuasive storytelling play a significant role in triggering impulse buying. Influencers are perceived as trusted references whose recommendations reduce cognitive evaluation and encourage spontaneous purchasing decisions. This study contributes to consumer behavior and influencer marketing literature by providing contextual insights into the psychological and relational mechanisms underlying impulse buying in FMCG contexts. Practically, the findings offer guidance for marketers in designing ethical and effective influencer strategies that consider consumer emotional responses.